Simulation Model Of An Air Freshener Flows In A Room By An Automatic Spray - Rozani, Nurul Rifhani (Universiti Sains Malaysia, 2021)
The worldwide air freshener market was worth $10,124.4 million in 2017 and is anticipated to be worth $13,279.1 million by 2025, growing at a CAGR (compound annual growth rate) of 3.5 percent between 2018 and 2025. The air freshener market has been divided into four segments: type, end-use, distribution channel, and region. The market has been divided into several types, including electric, spray, gel, and others. An air freshener is a product that releases a scent to remove unwanted odours from a space. For customer satisfaction, maximizing the scent of an air freseher in a space is of paramount importance. In this project, the circulation of an air-freshener flows in a particular space were studied to enhance the scent produced by an automatic spray. A simulation model of an automatic air freshener spray with a different number of it in the living room were presented to investigate the effect of the number of automatic spray in a room on scent circulation. The analysis results shows that the living room with the highest number of automatic air freshener has the highest percentage of the volume occupied with value of 0.95%. This project findings may contribute to guide customer purchases to enhance their satisfaction of the freshener product. Then will benefit the manufacturer.